A rapid and easy method for multiple endocrine neoplasia type 1 mutation detection using conformation-sensitive gel electrophoresis - Cebrián, Arancha; Ruíz-Llorente, Sergio; Cascón, Alberto; Osorio, Ana; Martínez-Delgado, Beatriz; Benítez, Javier; Robledo, Mercedes (Nature, 2002)
Until now, the study of the multiple endocrine neoplasia type 1 (MEN1) gene in patients suspected of having the disease was expensive and laborious due to the large size of the gene. We have optimized the conformation sensitive gel electrophoresis (CSGE) technique to analyze by four rather simple multiplex PCR reactions, and a single electrophoresis run, the entire coding region of the MEN1 gene, plus the exon¿intron boundaries. This improvement of the CSGE technique was confirmed as an effective proce dure for screening for the MEN1 gene by detecting ten previously known MEN1 gene mutations and four polymor phisms. The MEN1 gene of 12 patients with unknown mu tations was then screened, and an abnormal CSGE profile was identified in 10/12 cases. Subsequent DNA sequencing demonstrated 3 of them to be novel mutations (E45K, 4479delACAG, 6073insC) and 7 to have been previously reported; in the remaining 2 patients, we confirmed the absence of any alteration of the coding sequence of MEN1. Mutation screening of the MEN1 gene using CSGE was demonstrated to be a fast, simple, and inexpensive method to study patients suspected of having MEN1 disease.